2020
DOI: 10.1186/s13287-020-01837-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells inhibited the differentiation of MDSCs via COX2/PGE2 in experimental sialadenitis

Abstract: Background: Mesenchymal stem cells (MSCs) can regulate innate and adaptive immune systems through interacting with immune cells directly and secreting multiple soluble factors. Due to their immunosuppressive properties, MSC transplantation has been applied to treat many clinical and experimental autoimmune diseases. However, the therapeutic effects and mechanisms by which MSCs regulate myeloid cells in Sjögren's syndrome (SS) still remain elusive. Methods: The number and immune-suppressive activity of myeloid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Similarly, we found that PGE2 enhanced GM-CSF/IL-6-induced PMN- and M-MDSC activity through the EP4 receptor from cultured bone marrow cells. In line with these and related previous findings ( 23 , 25 27 ), we found that PGE2 upregulated Arg1 and Nos2 expression in murine bone marrow cells through the EP2 and EP4 receptors. As previously discussed, arginase-1 is one of the main products of MDSCs that contribute to their anti-inflammatory effector functions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, we found that PGE2 enhanced GM-CSF/IL-6-induced PMN- and M-MDSC activity through the EP4 receptor from cultured bone marrow cells. In line with these and related previous findings ( 23 , 25 27 ), we found that PGE2 upregulated Arg1 and Nos2 expression in murine bone marrow cells through the EP2 and EP4 receptors. As previously discussed, arginase-1 is one of the main products of MDSCs that contribute to their anti-inflammatory effector functions.…”
Section: Discussionsupporting
confidence: 93%
“…PGE2 has previously been used to enhance the generation of MDSCs from human PBMCs ( 21 ) and from murine bone marrow cells ( 22 , 23 ) in vitro . Shi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The method of MSC transplantation in mice and humans appeared to be broadly consistent across the studies. Intravenous injections of MSCs were used in all studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], with the exception of one [ 30 ] in which MSCs were administered intraperitoneally. A variety of cocultures were used such as UCMSCs cocultured with peripheral blood mononuclear cells (PBMCs) [ 31 , 32 ], and MSCs cocultured with monocyte-derived dendritic cells [ 26 ] or CD4 + T cells and MSC coculture experiments [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MDSCs phenotype differs between mice and humans. Mouse MDSCs are characterized as CD11b + Gr-1 + cells and can be further divided into CD11b + Ly6G low Ly6C high monocytic MDSCs (M-MDSCs) and CD11b + Ly6G high Ly6C low granulocytic MDSCs (G-MDSCs) (14). Human MDSCs are CD11b + CD33 + HLA-DRcells (15).…”
Section: Introductionmentioning
confidence: 99%